Day of the dead [large type] - French, Nicci (French, Nicci. Frieda Klein novel., 2018)
"A decade ago, psychologist Frieda Klein was sucked into the orbit of Dean Reeve -- a killer able to impersonate almost anyone, a man who can disappear without a trace, a psychopath obsessed with Frieda herself. In the years since, Frieda has worked with -- and sometimes against -- the London police in solving their most baffling cases. But now she's in hiding, driven to isolation by Reeve. When a series of murders announces his return, Frieda must emerge from the shadows to confront her nemesis. And it's a showdown she might not survive"--